Klotho and Aminopeptidases as Early Biomarkers of Renal Injury in Zucker Obese Rats - Montoro-Molina, Sebastián; López-Carmona, Antonio; Quesada, Andrés; O’Valle, Francisco; Martín-Morales, Natividad; Osuna, Antonio; Vargas, Félix; Wangensteen, Rosemary (Frontiers in Physiology, 2018)
The aim of this study was to investigate if urinary glutamyl aminopeptidase (GluAp), alanyl aminopeptidase (AlaAp), Klotho and hydroxyproline can be considered as potential biomarkers of renal injury and fibrosis in an experimental model of obesity. Male Zucker lean (ZL) and obese (ZO) rats were studied from 2 to 8 months old. Kidneys from ZO rats at the end of the study (8 months old) developed mild focal and segmental glomerulosclerosis as well as moderate tubulointerstitial injury. Urinary excretion of Klotho was higher in ZO rats at 2, 5 and 8 months of study, plasma Klotho levels were reduced and protein abundance of Klotho in renal tissue was similar in ZL and ZO rats. GluAp and AlaAp urinary activities also were also increased in ZO rats throughout the time-course study. ZO rats showed an augmentation of hydroxyproline content in renal tissue and a significant increase of tubulointerstitial fibrosis. Correlation studies demonstrated that GluAp, AlaAp and Klotho are early diagnostic markers of renal lesions in Zucker obese rats. Proteinuria and hydroxyproline can be considered delayed diagnostic markers because their contribution to diagnosis starts later. Another relevant result is that GluAp, AlaAp and Klotho are related not only with diagnosis but also with prognosis of renal lesions in Zucker obese rats. Moreover, strong predictive correlations of aminopeptidasic activities with the percentage of renal fibrosis or with renal hydroxyproline content at the end of the experiment were observed, indicating that an early increased excretion of these markers is related with a higher later extent of fibrosis in Zucker obese rats. In conclusion, GluAp, AlaAp and Klotho are early diagnostic markers that are also related with the extent of renal fibrosis in Zucker obese rats. Therefore, they have a potential use not only in diagnosis, but also in prognosis of obesity-associated renal lesions.